Resolution of headache after reduction of prolactin levels in hyperprolactinemic patients - OLIVEIRA, Miriam da Costa; BAREA, Liselotte Menke; HORN, Andreia Peres Klein; ONGARATTI, Bárbara Roberta; SOARES, José Otávio Dworzeki; ARAUJO, Bruna; SANTOS, Tainá Mafalda dos; RECH, Carolina Leães; PEREIRA-LIMA, Júlia Fernanda Semmelmann (Arquivos de Neuro-Psiquiatria, 2020)
Prolactin (PRL) secreting adenomas are associated with high incidence of headache. The role of hyperprolactinemia in the headache context is not clear, nor is the effect of its treatment on headache. Methods: The present longitudinal study evaluated hyperprolactinemic patients (69), in terms of presence and characteristics of headache before and after hyperprolactinemia treatment. Results: Headache was reported by 45 (65.2%) patients, independent of the etiology of hyperprolactinemia. The migraine phenotype was the most prevalent (66.6%). Medications used in the treatment of headache not changed during the study. The first line of treatment of hyperprolactinemia was dopaminergic agonists. In the last reevaluation, PRL level under treatment was within the reference range in 54.7% of the cases, and it was observed complete or partial resolution of the headache in 75% of the cases. The median PRL at this time in patients with complete headache resolution was 17 ng/mL, in those who reported partial recovery was 21 ng/mL, and in those in whom the headache did not change was 66 ng/mL, with a significant difference between the group with complete headache resolution vs. the group with unchanged headache (p=0.022). In the cases with complete headache resolution, the median fall on PRL levels was 89% and in those cases with partial headache resolution 86%, both significantly different (p<0.001) from the fall in the cases with an unchanged headache. Conclusion: Data allow us to conclude that, in this series, in the majority of cases the reduction in the level of PRL was followe3d by cessation or relief of the pain.
Keywords: headache; pituitary adenomas; prolactin; hyperprolactinemia; dopaminergic agonist